2017
DOI: 10.1111/beer.12151
|View full text |Cite
|
Sign up to set email alerts
|

Green intentions under the blue flag: Exploring differences in EU consumers’ willingness to pay more for environmentally‐friendly products

Abstract: Recent research on consumer social responsibility highlights the need to examine psychological drivers of environmentally‐friendly consumption choices in a global context. This article investigates consumers’ willingness to pay (WTP) more for environmentally‐friendly products across 28 European Union (EU) countries, using a sample of 21,514 consumers. A multigroup structural equation modeling analysis reveals significantly different patterns and relationships, in how (a) subjective knowledge about the product'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 110 publications
(160 reference statements)
2
30
0
Order By: Relevance
“…This shift is important since, in order to thrive in the future, businesses should have the ability to efficiently use their resources and develop their expertise to address the challenges of environmental constraints (Menguc and Ozanne 2005 ). Opportunities for environmentally sustainable actions by smaller businesses are also supported by the growing number of consumers who are willing to pay extra for eco-friendly products (Gregory-Smith et al 2017 ; Namkung and Jang 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This shift is important since, in order to thrive in the future, businesses should have the ability to efficiently use their resources and develop their expertise to address the challenges of environmental constraints (Menguc and Ozanne 2005 ). Opportunities for environmentally sustainable actions by smaller businesses are also supported by the growing number of consumers who are willing to pay extra for eco-friendly products (Gregory-Smith et al 2017 ; Namkung and Jang 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Ayuso, ; Rivera, ). Other studies have suggested that customers with a strong sustainability value can demand the increased integration of sustainability issues into the firms’ operations (Ayuso, ; Best & Thapa, ; Gregory‐Smith, Manika & Demirel, ). Second, organizations can also adopt certain practices through mimetic mechanisms (Meyer & Rowan, ; Scott, ).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…The stakeholders' awareness of social responsibility of firms have been increased. Firms, governments, regulatory authorities, investors and consumers all over the world pay more attention for environmental sustainability issues (Gregory-Smith et al 2017). The societies around the world are greatly concerned in recognizing that firms are really committed to environmental protection from issues like emissions, climate change, contamination, and other environmental influences arising from the operations of firms.…”
Section: Introductionmentioning
confidence: 99%